Kajian Konsep MIT 90’s Sebagai Salah Satu Kerangka Kerja untuk Membangun Sistem Informasi Bisnis - Angela Caroline (Maranatha University Press, 2018)
The development of information systems brings a big change to organizations and companies. Information systems can be utilized by the organization or company as core competencies because it can be used in assisting decision-making. This study aims to show the development of MIT 90's and demonstrate that MIT 90's is one of the best frameworks used to plan, develop and implement information systems. This study does not thoroughly describe the understanding and development of MIT 90's because this research has not examined all available sources. However, this study contributes to the improvement of MIT 90's theory and practice for the development of information systems within organizations and companies. The approach in this study was conducted by reviewing and synthesizing scientific papers and publications related to MIT 90’s. This study addresses the following: MIT 90's development seen from the definitions and factors (elements) within the MIT 90's; MIT 90's supporting factors as a framework for building information systems; implementation of MIT 90's to help organizations and companies build appropriate information systems. The results show that MIT 90's is suitable to be used as one of the frameworks for building information system.